Aerobic, Palladium-Catalyzed Dioxygenation of Alkenes Enabled by Catalytic Nitrite - Wickens, Zachary K. (Angew Chem Int Ed Engl, 2014)
Catalytic nitrite was found to enable carbon-oxygen bond-forming reductive elimination from unstable alkyl palladium intermediates, providing dioxygenated products from alkenes. A variety of functional groups are tolerated and high yields (up to 94%) are observed with many substrates, including a multi-gram scale reaction. Nitrogen dioxide, which could form from nitrite under the reaction conditions, was shown to be kinetically competent in the dioxygenation of alkenes. Furthermore, the reductive elimination event was probed with (18) O-labeling experiments, which demonstrated that both oxygen atoms in the difunctionalized products are derived from one molecule of acetic acid.